2018
DOI: 10.1007/s10902-018-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Mediating Roles of Strengths Knowledge and Strengths Use in a 1-Year Single-Session Character Strength-Based Cognitive Intervention

Abstract: Character strength-based interventions are an effective positive psychology approach in increasing happiness and reducing depression. However, little is known about whether the character strength-based interventions remain effective over an extended time period of 1 year, and why these activities (e.g., Identifying signature strengths and Using signature strengths in a new way) work. To address these issues, a 1-year randomized controlled intervention was conducted to examine the serial mediating role of stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
(52 reference statements)
1
30
0
1
Order By: Relevance
“…Self-determination theory likewise indicates that the fulfillment of psychological needs for competence enhances personal developments and well-being (Ryan and Deci, 2000, 2001). Strength use could be practiced and developed over time and then deliver sustainable benefits, but strength knowledge could move from “no” (strengths knowledge = 0) to “have” (strengths knowledge = 1) and then deliver an initial benefit (Duan et al, 2018a). Thus, as suggested by Duan et al (2018a), strength knowledge can be set as a binary variable to investigate its role between character strengths and outcomes in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-determination theory likewise indicates that the fulfillment of psychological needs for competence enhances personal developments and well-being (Ryan and Deci, 2000, 2001). Strength use could be practiced and developed over time and then deliver sustainable benefits, but strength knowledge could move from “no” (strengths knowledge = 0) to “have” (strengths knowledge = 1) and then deliver an initial benefit (Duan et al, 2018a). Thus, as suggested by Duan et al (2018a), strength knowledge can be set as a binary variable to investigate its role between character strengths and outcomes in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, Quinlan et al (2015) attempted a six-session intervention with 9- to 12-year-old students and found that rather than strength knowledge, strength use was associated with well-being changes and achievements. Thereafter, in a 1-year randomized controlled intervention Duan et al (2018a) found that changes in strength use were significantly correlated with well-being, whereas changes in the awareness and recognition of character strengths did not significantly predict well-being. Thus, believing that strength use rather than strength knowledge was the working component is reasonable.…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous experiences (Duan & Bu, 2019; Duan et al, 2019), we believe that combining strength-based strategies with the traditional WBT is reasonable to construct an SFI. For example, the character strength–based cognitive intervention (SCI; Duan & Bu, 2019; Duan et al, 2019) equips the existing CBT model with character strengths (i.e., positive personal assets; Peterson & Seligman, 2004) by conducting two successive intervention sections, that is, cognition (which focuses on the awareness and exploration of an individual’s signature strengths) and behavioral (which focuses on the application of an individual’s signature strengths) sections. The effectiveness of SCI in promoting well-being and alleviating negative emotions has been repetitively shown in existing literature (Duan & Bu, 2019; Duan et al, 2019).…”
Section: Sfi Developmentmentioning
confidence: 92%
“…The Chinese versions of Strength Knowledge Scale (SKS, eight items) and Strength Use Scale (SUS, 14 items) were used for manipulation check, measuring the awareness and utilization of participants’ character strengths (Duan et al, 2017; Govindji & Linley, 2007). SKS and SUS have demonstrated intervention benefits in previous character SCIs (Duan & Bu, 2019; Duan et al, 2019). Each item of SKS (e.g., “I know when I am at my optimal condition”) and SUS (e.g., “I can use my strengths in different situations”) was constructed as a 7-point Likert-type scale (1 = strongly disagree ; 7 = strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation